Network Pharmacology Identifies AKT1, SRC, and STAT3 as Therapeutic Targets of Tempeh-Derived Peptides in Breast Cancer - Takawaian, Agrita Feisilia; Antasionasti, Irma; Tallei, Trina Ekawati (Malacca Pharmaceutics, 2025)
Breast cancer remains a major cause of mortality among women, particularly the aggressive subtypes HER2-positive and triple-negative breast cancer (TNBC). Fermented foods such as tempeh contain bioactive peptides with potential therapeutic properties, including anticancer activity, yet their molecular mechanisms in cancer remain unclear. This study aimed to investigate the potential of tempeh-derived peptides as anti-breast cancer agents using a network pharmacology approach integrated with molecular docking. Tempeh peptides were collected from previously published literature. Target genes of tempeh-derived peptides were predicted and compared with breast cancer–associated genes to identify overlapping candidates. These were analyzed through protein–protein interaction networks and subjected to functional and pathway enrichment to uncover key molecular mechanisms. The results showed that tempeh-derived peptides are closely linked to key oncogenic pathways, including PI3K-Akt, ErbB, MAPK, JAK-STAT, and general cancer signaling. Protein–protein interaction network analysis highlighted AKT1, SRC, STAT3, and PIK3CA as central hub proteins with well-established roles in regulating proliferation, migration, angiogenesis, and survival. AKT1 is strongly connected to HER2-driven signaling, SRC is involved in both HER2+ and therapy-resistant TNBC, STAT3 is critically implicated in TNBC biology, and PIK3CA functions as a pivotal upstream regulator of AKT1, underscoring their therapeutic significance. Molecular docking confirmed strong binding affinities of peptides such as Trp-Met-Phe-Asp-Trp, Pro-Phe-Tyr-Phe, and Trp-Met-Gly-Pro-Tyr to these hubs, suggesting disruption of phosphorylation-dependent activation and downstream oncogenic cascades. These findings support the potential of tempeh-derived peptides as multi-target modulators in aggressive breast cancer subtypes and highlight the need for experimental validation to advance their therapeutic application.